POVERTY, RAPE VICTIMS AND SOCIAL STRUCTURE: A STUDY ON A MARRIAGE INSTITUTION IN THE INTERFACE: CASE STUDIES OF KHUNTI AND GUMLA DISTRICTS OF JHARKHAND - Kumari, Deepa; Chaudhuri, Sucheta Sen (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Micro studies as a perspective is inevitable to examine problems of the society. This research article concentrates to understand social impediments against victims of rapes from the perspective of poverty, gender, and community interface. Field work experiences reveal that the administrators, security personnel have misconceptions about tribal marriage institutions. Most importantly, the problem is that the tribal rape victims are treated differently due to misconceptions of the administrators. At this background present research article concentrates to understand different aspects and meanings of the “Dhuku” marriage institution of the Munda, Oraon and Ho from insiders’ perspectives and critical view point from the outsider’s perspective. Present study considers following variables like ‘poverty’ and ‘gender’ for analyzing the problem. Interviews were conducted and case studies are presented. Nineteen case studies presented among which ten respondents are insiders and nine outsiders. This paper recommends practical solutions to address problems of tribal women and men victims.